A Method Based on Logarithmic Spiral Edge Fitting for Information Extraction of Eddy in the SAR Image - Yang Min; Chong Jin-song (Leida xuebao, 2013)
The Synthetic Aperture Radar (SAR) provides abundant data for the research of eddies. It is important to extract the information of eddies in the SAR image effectively. In this paper, a method based on logarithmic spiral edge fitting for information extraction of eddy in the SAR image is presented, which is capable to extract the eddy center, eddy diameter, and the size of eddy edge. Based on this method, an experiment is conducted to extract the information of eddy in the sequential SAR images acquired by ENVISAT ASAR and ERS-2. The information of two eddies and their movement can be achieved. The validity of the method can be verified by comparing with the pseudo-color composite results.